Diode Laser-Assisted Surgical Therapy for Early Treatment of Oral Mucocele in a Newborn Patient: Case Report and Procedures Checklist - Marina Consuelo Vitale; Maria Francesca Sfondrini; Giorgio Alberto Croci; Marco Paulli; Lorenzo Carbone; Paola Gandini; Andrea Scribante (Case Reports in Dentistry)
Mucocele (also known as ranula or salivary gland mucous cyst) of the newborn is a lesion present on the intraoral cavity, with the potential to interfere with respiration and feeding. In the present report, a case of mucocele in a 4-month female patient has been described. As conventional surgery can be followed by several complications such as intraoperative bleeding, difficulties in wound healing, and maintenance of sterility during surgery, in the present case, the use of diode laser has been planned. A topic anesthesia with lidocaine gel was performed. A diode laser (810 nm wavelength, continuous wave mode, power output of 3 watt, and 0.4 mm diameter fiber optic) was set for excising the lesion. The tip was directed at an angle of 10 to 15°, moving around the base of the lesion with a circular motion. The procedure was completed in 3 minutes. The patient was visited with a follow-up of 2 weeks and 4 months after excision. The intraoral wound healed without complications, and no signs of infection or mass recurrence were noted. The histopathological examination confirmed the diagnosis of mucocele. On the basis of the results of the present case report, the use of diode laser can be easily performed also in a noncompliant newborn patient for successful excision of mucocele lesions, and checklist of clinical procedures has been described.